Training an innovative professional using active learning methodologies: intervention assessment (Research, Society and Development, 2021)
This study aims to verify the efficiency and effectiveness of a proposal to implement active learning methodologies in the Civil Engineering course of an institution in the interior of Piauí, aimed at training an innovative professional. The Action Plan, elaborated for the implementation of these methodologies, which presented 23 actions, of which 13 were executed, was evaluated. Subsequently, 39 students participated in the application of a questionnaire. The sample agrees that the actions provided engagement and participation of teachers, reporting the need to improve aspects such as optimization of classes in the new laboratories and innovation room and in the way of using the tools of active methodologies. Then, 12 professors of the course and coordinator participated in a focus group. For the qualitative analysis of the data collected in the focus group, the R Interface pour les Analyzes Multidimensionnelles by Textes et de Questionnaires (IRAMUTEQ) was used, a free program that allows different forms of statistical analysis on textual corpus and on tables of individuals by words. From this analysis, the ramifications "Technology and education" and "The new profile of graduates and the labor market" emerged, which were in line with what the study had already defined in relation to the needs of implementing a new institutional culture, environments and adequate equipment, teacher training, skills development and innovation for the labor market. Finally, it is concluded that the adopted model constituted an efficient instrument for the implementation of active methodologies in the Civil Engineering course and can be used in other courses of the institution in which the study was developed and in other higher education institutions that intend to implement the tools of active methodologies as well as being able to serve as a basis for future studies on this theme.